Human Resource Management in Context / Insights, Strategy and Solutions - Farnham David (Cipd (Chartered Institute of Personnel and Development), 2015)
Built around five major themes which impact upon the HR function, and mapping to the CIPD level 7 module for the same name, this book will enable the reader to understand the complex and changing organizational context in which HR operates today by providing a comprehensive breakdown of the concepts, theories and issues associated with external and internal contexts. List of Figures and Tables, Preface, HRM and Organizations and Management, Human Resource Management and its External Contexts, Contemporary Organizations and their Internal Contexts, The Managerial and Business Contexts of Organizations, Strategy Formulation and Implementation, Developing Corporate Strategies, Developing Human Resource Strategies, The External Contexts of Human Resource Management, Markets and the Competitive Context, Globalization and International Factors, Demographic and Social Trends, The Technological Context, Government Policy and Legal Regulation, Bibliography, Index.